Multi-station positioning accuracy and enhancement method for 5G - Feilong ZHAO; Lili WANG (物联网学报)
RAT-dependent is a satellite independent positioning technology of 5G.3GPP gives the Cramer-Rao lower bound (CRLB) of the positioning accuracy under the ideal condition of a single station and the simulation positioning accuracy of multi-station under different network configurations.Based on the actual network conditions, the analysis framework, accuracy range of multi-station positioning accuracy and the corresponding improvement method were proposed.The experimental results show that the RAT-dependent positioning accuracy is closely related to network technologies, and the positioning accuracy of the optimized scheme can be improved by 20%～30% compared with the non-optimized scheme.